Financial Reporting Rules and Corporate Decisions: A Study of Public Policy (Book). - Meyer, Philip E.; Griffin, Paul A. (The Accounting Review, 1983)
Reviews the book "Financial Reporting Rules and Corporate Decisions: A Study of Public Policy," by Bertrand Horwitz and Richard Kolodny.